The Missouri compromise - Thompson, Helen B. (My University, 1903)
Introduction: In the beginning of the nineteenth century, President Jefferson effected the transfer of Louisiana. The Possession of the mouth of the Mississippi River was a commercial necessity, and Jefferson showed wisdom in seizing the opportunity presented by a fortunate combination of circumstances to secure the purchase of this magnificent domain from the French government. The acquisition of Louisiana brought incalculable wealth, power and prestige to the union, and must always be regarded as the master-stroke of policy which advanced the United States from a comparatively feeble nation, lying between the Atlantic and the Mississippi, to a continental power of assured strength and boundless promise. The state of Louisiana having been formed from the southern part of this great tract in 1812, that portion of the purchase north of the thirty-ninth parallel took the name of Missouri Territory.
Citation: Thompson, Helen B. The Missouri compromise. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Protedctive Ckoloration; Warning Colors; Mimicry; Theses